Smyd1 Orchestrates Early Heart Development Through Positive and Negative Gene Regulation - Wang, Zhen; Schwartz, Robert J.; Liu, Jing; Sun, Fei; Li, Qi; Ma, Yanlin (Frontiers in Cell and Developmental Biology, 2021)
SET and MYND domain-containing protein 1 (Smyd1) is a striated muscle-specific histone methyltransferase. Our prior work demonstrated that deletion of Smyd1 in either cardiomyocytes or the outflow tract (OFT) resulted in embryonic lethality at E9.5, with cardiac structural defects such as truncation of the OFT and right ventricle and impaired expansion and proliferation of the second heart field (SHF). The cardiac phenotype was accompanied by the down-regulation of Isl1and and upregulation of ANF. However, the mechanisms of Smyd1 regulating Isl1 and ANF during embryonic heart development remain to be elucidated. Here, we employed various biochemical and molecular biological approaches including chromatin immunoprecipitation polymerase chain reaction (ChIP-PCR), real-time PCR, pGL3 dual fluorescence reporter system and co-Immunoprecipitation (CoIP) and found that the Smyd1 interacted with ASH2L and activated the promoter of Isl1 by trimethylating H3K4. We also found that Smyd1 associated with HDAC to repress ANF expression using trichostatin A (TSA), a deacetylase inhibitor. In conclusion, Smyd1 participates in early heart development by upregulating the expression of Isl1 and down-regulating the expression of ANF.